2012
DOI: 10.1038/jhh.2012.15
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional single-nucleotide polymorphism in the ALDH2 gene with essential hypertension depends on drinking behavior in a Chinese Han population

Abstract: Alcohol consumption is an important environmental factor in the development of essential hypertension (EH) and cardiovascular disease. Several epidemiological studies have investigated the association between hypertension and acetaldehyde dehydrogenase 2 (ALDH2) genotype, although the results are inconsistent. The aim of the present study was to evaluate the possible effect of drinking behavior on the ALDH2-EH relationship in a Chinese Han population. A total of 1098 unrelated individuals with EH and 1021 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…A recent study reported that ALDH2 is related to chronic age-associated diseases such as coronary artery disease and hypertension 11). Seok et al,12) conducted a study on the relationship between missense ALDH2 (SNP: Glu504Lys) and benign prostatic hyperplasia in Koreans.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that ALDH2 is related to chronic age-associated diseases such as coronary artery disease and hypertension 11). Seok et al,12) conducted a study on the relationship between missense ALDH2 (SNP: Glu504Lys) and benign prostatic hyperplasia in Koreans.…”
Section: Introductionmentioning
confidence: 99%
“…133 The mutation behaves in an over-dominant fashion so that ALDH2 enzymatic activity is reduced to 20-35% of wild type enzyme in heterozygous individuals. Recent genome-wide association and epidemiological studies provide strong evidence linking ALDH2*2 genotype with the risk of coronary artery disease (CAD), 134,135 MI, 136 hypertension, 137 dyslipidemia, 138 and hyperglycemia. 139 The elevated health risk of cardiovascular diseases that many East Asians may face due to the ALDH2*2 further demonstrates the relevance of ALDH2 as a cardiovascular therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that the mechanism is closely related to decreased alcohol consumption. After adjusting for alcohol consumption, the *504Lys allele and hypertension were no longer correlated (Takagi et al 2001;Amamoto et al 2002;Wang et al 2013). However, other studies have demonstrated that the mechanism is not related to alcohol consumption (Hui et al 2007;Hasi et al 2011).…”
Section: Traditional Cardiovascular Risk Factorsmentioning
confidence: 84%